Photovoice: An Alternative Method for Inclusive Research in Re- vealing the Collective Memory of Space and Identity in Salatiga - Sukmi, Sih Natalia; Kristiyani, Dian Novita (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2026)
Communication studies increasingly confront the complexity of social spaces and the need for inclusivity. This study explores the implementation of photovoice as an alternative method for inclusive research, aiming to provide equal participation for youth communities in Salatiga, including individuals with disabilities. The research seeks to uncover how collective memory and urban identity are constructed through visual narratives and participatory engagement. Employing a qualitative approach within a constructivist paradigm, data were collected from 14 informants through focus group discussions, interviews, and 30 photographs, then analyzed using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) framework. Findings indicate that photovoice facilitates participants’ reflection on spatial experiences and personal memories, encouraging dialogue across diverse backgrounds. It strengthens participants’ roles as co-creators of knowledge and offers a visual platform for expressing marginalized perspectives. Despite interpretative challenges, photovoice proves effective in revealing lived experiences and fostering inclusivity. The study concludes that photovoice serves as an innovative and participatory approach to inclusive research. Its broader implication emphasizes the potential of visual methods to democratize knowledge production, enhance equitable representation, and contribute to the reconstruction of urban and cultural identities within contemporary communication studies.